If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = (-2x) + 4 Reorder the terms: 19 = 4 + (-2x) Solving 19 = 4 + (-2x) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(2x)' to each side of the equation. 19 + (2x) = 4 + (-2x) + (2x) Combine like terms: (-2x) + (2x) = 0 19 + (2x) = 4 + 0 19 + (2x) = 4 Add '-19' to each side of the equation. 19 + -19 + (2x) = 4 + -19 Combine like terms: 19 + -19 = 0 0 + (2x) = 4 + -19 (2x) = 4 + -19 Combine like terms: 4 + -19 = -15 (2x) = -15 Divide each side by '2'. x = -7.5 Simplifying x = -7.5
| 9-3p=8 | | 2x^2+50x+9=5 | | 4x^2-15x-97=0 | | 0.5x+19.3=x-5.55 | | 2x^2+693=4x | | 0.9x+2.64=-0.5x+0.64 | | x^3+5x^2-10x=0 | | 600x-0.32=400x+0.94 | | 9.7=8x+2.5 | | (4x-1)(x)=18 | | y-2.2=10 | | 4x-26.7=x | | 7(x-1.8)=7.7 | | 8.2y+6.99=-64.35 | | 3x+16=2x+10 | | 72x^4+132x^3-36x^2-24x=0 | | x+3.1=6.4 | | 15=z-14 | | (11x+z)(11x-z)=0 | | m-31=-7 | | 3(x+1)=8(x-2)-16 | | (5a+6)(9a^2-8a-4)=0 | | 400x-0.21=600x+0.89 | | 3x+3(5x-7x)=12x-x | | 9x-2=7x-8 | | (3x+7)(2x-1)=0 | | 7p-3=2p+2 | | 5x-7x+24=5x+38 | | 7x+3x-6x=5+7 | | 5b-0.5=6b | | 2(x+5)=3(x-1) | | 117=-39k |